2011
DOI: 10.1051/mbcb/2011145
|View full text |Cite
|
Sign up to set email alerts
|

Etude immunohistochimique des facteurs de la prolifération (Ki67, PCNA) et de l’apoptose (P53) sur 40 kératokystes odontogénes

Abstract: Résumé -Introduction : le kératokyste odontogéne (KKO) est une des tumeurs odontogènes les plus fréquentes. Plusieurs travaux se sont intéressés à l'étude de cette lésion depuis sa première description afin de pouvoir comprendre son comportement biologique. Matériel et méthode : il s'agit d'une étude rétrospective immunohistochimique des marqueurs PCNA, Ki67 et P53 chez 40 patients opérés pour un KKO. Résultats : ces marqueurs sont retrouvés dans les couches suprabasales de l'épithélium de la paroi kystique. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…16,20 In odontogenic benign tumors, ameloblastoma is the most common lesion according to literature. 7,20 These results are similar to those observed in this study with a predominance of ameloblastoma found in 50.9% of the collected surgical specimens. The follicular and plexiform histological types are the most frequently described in literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16,20 In odontogenic benign tumors, ameloblastoma is the most common lesion according to literature. 7,20 These results are similar to those observed in this study with a predominance of ameloblastoma found in 50.9% of the collected surgical specimens. The follicular and plexiform histological types are the most frequently described in literature.…”
Section: Discussionsupporting
confidence: 90%
“…Among these markers, the (Ki67) cell proliferation index is a biological marker for assessing the proliferative capacity of tumor cells. [7][8][9][10] In fact, the Ki67 is a nuclear protein expressed during the G1, S, G2 and M phases of the cell cycle and not during the G0 quiescence phase.…”
Section: Introductionmentioning
confidence: 99%